Natural active products in fruit postharvest preservation: A review - Yufeng Sun; Ran Tao; Yang Ju; Jiajing Duan; Qinfei Xie; Bei Fan; Fengzhong Wang (Food Frontiers)
Abstract Abundantly available plants, animals, and microbes are excellent source of active substance to be used as fruit preservatives to delay postharvest fruit from decay, maintain good quality, and increase the shelf life. Although they are effective and free from toxicological risks, the use of the natural active products in agriculture is still limited due to the high cost of producing, complexity interaction in food matrix, and unacceptance of odor. This review focuses on employing naturally occurring bioactive compounds as an alternative to the synthetic preservatives used in fruit. For this purpose, natural compounds from abundantly available source, such as plants, animals, and microbes, are systematically described for their properties, mechanism of action, and applicability. Different postharvest handling of bioactive compounds and mechanism of their triggered/controlled release properties are discussed, especially with regard to challenge and future directions of these new strategy to preserve fruit in industry. This review offers a fundamental theory and technologies to develop the efficient and safe alternative strategies to synthetic fruits preservatives. Overall, the utilization of natural preservative techniques offers promising opportunities to maintain quality and extend shelf life of fruit, with potential applications in various industries such as vegetables, meat, and processed food.